Geometric entities information for feature extraction of solid model based on DXF file - Sukimin, Zuraini (2008)
In recent years, various researchers have come up with different ways and means in identifying geometric entities for feature extraction. Automated extraction of features on determination a geometric entity of solid model becomes as one of the core tasks in CAD/CAM. In this research, we have adopted the latter approach by examining DXF format as the base of the 3D object. By using the DXF file, explained the structure of the file format that consists of six sections which are HEADER, CLASSES, BLOCKS, TABLES, OBJECT and ENTITIES. The structured of the proposed methodology consist of three main phase. First phase is exporting the CAD file to DXF code as an input to the second phase. The second phase, the code is classified to the categories it is belong to in facilitating the recognition of entities in geometry. Lastly, the third phase is maps the extracted features as it supposedly appear.